Orthohantaviruses belonging to three phylogroups all inhibit apoptosis in infected target cells - Solà-Riera, Carles; Gupta, Shawon (Scientific reports, 2019)
Orthohantaviruses, previously known as hantaviruses, are zoonotic viruses that can cause hantavirus pulmonary syndrome (HPS) and hemorrhagic fever with renal syndrome (HFRS) in humans. The HPS-causing Andes virus (ANDV) and the HFRS-causing Hantaan virus (HTNV) have anti-apoptotic effects. To investigate if this represents a general feature of orthohantaviruses, we analysed the capacity of six different orthohantaviruses - belonging to three distinct phylogroups and representing both pathogenic and non-pathogenic viruses - to inhibit apoptosis in infected cells. Primary human endothelial cells were infected with ANDV, HTNV, the HFRS-causing Puumala virus (PUUV) and Seoul virus, as well as the putative non-pathogenic Prospect Hill virus and Tula virus. Infected cells were then exposed to the apoptosis-inducing chemical staurosporine or to activated human NK cells exhibiting a high cytotoxic potential. Strikingly, all orthohantaviruses inhibited apoptosis in both settings. Moreover, we show that the nucleocapsid (N) protein from all examined orthohantaviruses are potential targets for caspase-3 and granzyme B. Recombinant N protein from ANDV, PUUV and the HFRS-causing Dobrava virus strongly inhibited granzyme B activity and also, to certain extent, caspase-3 activity. Taken together, this study demonstrates that six different orthohantaviruses inhibit apoptosis, suggesting this to be a general feature of orthohantaviruses likely serving as a mechanism of viral immune evasion.
Gesehen am 25.02.2019